NF-κB/IL-6 axis drives impaired corneal wound healing in aqueous-deficient dry eye - Lin, Cuipei; Wu, Jiaxin; Jing, Yuxin; Xie, Jingbin; Xiang, Jiayan; Fan, Qiwei; Liu, Jiangman; Du, Jingheng; Tan, Xiukui; Zhuang, Zhudan; Xue, Yunxia; Fu, Ting; et al. (Frontiers in Immunology, 2025)
Dry eye disease (DED) commonly leads to compromised corneal epithelial integrity and chronic ocular surface inflammation; however, the precise molecular mechanisms underlying impaired corneal healing remain incompletely understood. In this study, we established an aqueous‐deficient DED mouse model via extraorbital lacrimal gland excision (LGE) to investigate the cellular and molecular events contributing to delayed corneal repair following epithelial injury. Our results demonstrated significant delays in corneal re‐epithelialization and nerve regeneration in aqueous‐deficient mice, accompanied by increased infiltration of neutrophils and γδ T cells. Transcriptomic profiling revealed robust activation of NF‐κB‐dependent inflammatory signaling and IL‐6 pathways, alongside marked suppression of genes associated with essential metabolic processes involved in tissue repair. Targeted pharmacological inhibition of NF‐κB using caffeic acid phenethyl ester (CAPE), or neutralization of IL‐6 via topical anti-IL‐6 antibody administration, effectively attenuated immune cell infiltration, accelerated epithelial regeneration, and enhanced nerve recovery. Collectively, our findings suggest that NF-κB/IL-6 signaling plays a key role in sustaining inflammation that impairs corneal healing, and that targeting this axis partially improves epithelial and neural outcomes.